2020
DOI: 10.1371/journal.pone.0234803
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of body weight in wild populations of medaka fish from different latitudes

Abstract: The genetic bases of growth and body weight are of economic and scientific interest, and teleost fish models have proven useful in such investigations. The Oryzias latipes species complex (medaka) is an abundant freshwater fish in Japan and suitable for genetic studies. We compared two wild medaka stocks originating from different latitudes. The Maizuru population from higher latitudes weighed more than the Ginoza population. We investigated the genetic basis of body weight, using quantitative trait locus (QTL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 55 publications
1
5
0
Order By: Relevance
“…This finding lends support to a hypothesis of size‐related positive heterosis wherein measures of fitness and fitness proxies such as size (Kingsolver and Pfennig 2004) may be elevated in first‐generation crosses but reduced in subsequent generations (Lamkey and Edwards 1999; Bartley et al 2000; Ou et al 2019). Similar findings were observed in laboratory crosses of a model fish, with F 1 hybrids being generally larger than F 2 hybrids and intermediate in size to the parental forms (Yassumoto et al 2020), and in cichlid fishes, for which fitness was greater in F 1 hybrids than in F 2 hybrids (Stelkens et al 2015). In contrast, for the Micropterus genus, a lack of heterosis has been observed across multiple physiological factors (Williamson and Carmichael 1986; Cooke et al 2001; Philipp et al 2002; Cooke and Philipp 2006; Allen et al 2009).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…This finding lends support to a hypothesis of size‐related positive heterosis wherein measures of fitness and fitness proxies such as size (Kingsolver and Pfennig 2004) may be elevated in first‐generation crosses but reduced in subsequent generations (Lamkey and Edwards 1999; Bartley et al 2000; Ou et al 2019). Similar findings were observed in laboratory crosses of a model fish, with F 1 hybrids being generally larger than F 2 hybrids and intermediate in size to the parental forms (Yassumoto et al 2020), and in cichlid fishes, for which fitness was greater in F 1 hybrids than in F 2 hybrids (Stelkens et al 2015). In contrast, for the Micropterus genus, a lack of heterosis has been observed across multiple physiological factors (Williamson and Carmichael 1986; Cooke et al 2001; Philipp et al 2002; Cooke and Philipp 2006; Allen et al 2009).…”
Section: Discussionsupporting
confidence: 67%
“…For weight-class definitions, see Figure 2; for genotype definitions, see Figure 3. (Yassumoto et al 2020), and in cichlid fishes, for which fitness was greater in F 1 hybrids than in F 2 hybrids (Stelkens et al 2015). In contrast, for the Micropterus genus, a lack of heterosis has been observed across multiple physiological factors (Williamson and Carmichael 1986;Cooke et al 2001;Cooke and Philipp 2006;Allen et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Despite extensive molecular efforts to understand the genomic architecture underlying these traits, incongruent findings suggest that growth and maturation in teleosts may not share large-effect genes or similar regulatory checkpoints (Ali et al, 2020;Gong et al, 2022;Wang et al, 2015;Yassumoto et al, 2020;Zhou et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the investigation of responses of gonads under different photoperiods using populations collected in Hakodate (the northern location of Japan: cool-temperate zone) and Okinawa (the southern location of Japan: subtropical zone), a preliminary study suggested that local medaka populations from different latitudes had different responses to photoperiods [ 23 ]. Intra-specific variations in responses to changing photoperiods could contribute to investigating the genetic basis underlying photoperiod perception through forward genetic approaches using medaka [ 24 – 26 ].…”
Section: Introductionmentioning
confidence: 99%